Optimizing Human-AI Collaboration in Educational Administration in Muara Bungo, Jambi: An HRD Framework for Role Redefinition, Skill Development, and Change Management - Ariyanto Masnun; Silvia Jessika; Syah Amin Albadry; Hamirul (Enigma in Education, 2024)
Artificial Intelligence (AI) presents transformative potential for enhancing efficiency and effectiveness in educational administration. However, successful integration necessitates a strategic approach to managing the human element, including evolving roles, requisite skills, and organizational change. This study addressed the gap in targeted frameworks for optimizing human-AI collaboration within the specific context of educational administration in Muara Bungo, Jambi, Indonesia. A mixed-methods, quasi-experimental pre-post design was employed. Data were collected from 50 educational administrative staff in Muara Bungo using surveys assessing AI perceptions, skill readiness, and job satisfaction, alongside semi-structured interviews exploring experiences with role changes and change management. A bespoke Human Resource Development (HRD) framework, encompassing structured role redefinition workshops, targeted AI literacy and collaboration skill training modules, and a multi-faceted change management communication plan, was developed and implemented over six months. Quantitative data were analyzed using descriptive statistics and paired t-tests, while qualitative data underwent thematic analysis. Post-intervention, quantitative analysis revealed statistically significant improvements (p < 0.05) in participants' perceived usefulness of AI (t(49)=5.82), confidence in collaborating with AI tools (t(49)=6.15), and reported efficiency in administrative tasks (t(49)=4.98). Qualitative findings indicated that the HRD framework facilitated a clearer understanding of new roles, reduced initial anxiety towards AI, and highlighted the importance of ongoing support and transparent communication during the transition. In conclusion, the study demonstrated that a context-specific HRD framework integrating role redefinition, skill development, and change management can significantly enhance human-AI collaboration in educational administration. The findings underscore the necessity of proactive HRD interventions to equip staff, manage transitions effectively, and harness the synergistic potential of humans and AI in improving administrative functions within educational institutions in regions like Muara Bungo.